Habitat preference of Geometridae species in Western Black Sea region of Turkey (Lepidoptera: Geometridae) - M. Özdemir (SHILAP, 2019)
In this study, 3399 specimens belonging to 188 species of the Geometridae (Lepidoptera) family were examined. Species composition and abundance rates of Geometridae communities were analyzed with respect to the plant formations of the region as deciduous forests, dry coniferous-oak forests, humid coniferous forests, pseudomaquis and farmlands. The results also indicates that 26 species in deciduous forests, 23 species in coniferous-oak forests, 20 species in humid coniferous forests, 20 in pseudomaquis and 20 species in farmlands have high abundance rate. The highest rates of abundance in deciduous forests and dry coniferous-oak forests belong to Cyclophora linearia (Hübner, [1799]) with 14,7% and Peribatodes rhomboidaria ([Denis & Schiffermüller], 1775) 13,1%, respectively. Also, the highest rates of abundance in humid coniferous forests and pseudomaquis belong to Scotopteryx moeniata (Scopoli, 1763) with 23,46% and Cyclophora puppillaria (Hübner, [1799]) with 19,83%. Species richness is much higher in deciduous forests than it is in other habitats. Faunal similarities between the Geometridae communities are reported below 50% among all habitats. The highest faunal similarity was found to be between dry coniferous-oak forests followed by the second highest similarity between pseudomaquis and deciduous forests.